1995
DOI: 10.1007/bf01957507
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin levels in febrile and afebrile seizures

Abstract: Transient hyperprolactinaemia has been reported to follow unprovoked seizures, a finding proposed to be useful in the differential diagnosis of epilepsy. There is also evidence that patients with unprovoked seizures may have high baseline prolactin levels, which could be of value in detecting those predisposed to epilepsy after a first convulsive attack. The purpose of this study was to examine whether prolactin levels are elevated: (1) postictally in febrile seizures and (2) interictally in afebrile seizures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They found signifi cantly higher serum PL levels in the ES group. In typical FS, sub-clinical electrical activity does not exist, since the after-discharges are less intense and transient to project to the ventromedial hypothalamus, whereas, conditions mimicking seizures completely lack electrical discharges, which accounts for lack of PL elevation in conditions mimicking seizures 16 . In a study conducted by Banerjee et al 2 , 80% of children with GTCS and 60% with CPS had elevated serum PL level.…”
Section: Discussionmentioning
confidence: 99%
“…They found signifi cantly higher serum PL levels in the ES group. In typical FS, sub-clinical electrical activity does not exist, since the after-discharges are less intense and transient to project to the ventromedial hypothalamus, whereas, conditions mimicking seizures completely lack electrical discharges, which accounts for lack of PL elevation in conditions mimicking seizures 16 . In a study conducted by Banerjee et al 2 , 80% of children with GTCS and 60% with CPS had elevated serum PL level.…”
Section: Discussionmentioning
confidence: 99%
“…Fein in a study of 35 children noted a PPV of 65 % and NPV of 76 % in the diagnosis of tonic-clonic seizures [3]. Likewise, hyperprolactinemia has been reported to follow febrile seizures, as well as noting an 83 % increase from baseline of 202 to 370mU/l in this clinical setting [4]. Interestingly, there seems to be a tachyphylaxis-like response with depletion of the releasable protein.…”
Section: Discussionmentioning
confidence: 93%
“…5 Cortisol and prolactin levels were elevated in patients during the postictal period compared with control groups. 15,16 One study suggested that transient elevation of prolactin levels can differentiate an epileptic seizure from a nonepileptic movement that resembles seizure. 17 Seizure causes a significant and sustained elevation of thyrotropin releasing hormone (TRH) in specific extrahypothalamic rat brain regions related to epileptic foci such as the amygdala, hippocampus, pyriform cortex, and anterior cortex.…”
Section: Discussionmentioning
confidence: 99%